2022
DOI: 10.3390/ijms23126456
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between the Cytokine IL-37 and Thyroid Hormones in Modulating Chronic Inflammation Associated with Target Organ Damage in Age-Related Metabolic and Vascular Conditions

Abstract: Chronic inflammation is considered to be the main mechanism contributing to the development of age-related metabolic and vascular conditions. The phases of chronic inflammation that mediate the progression of target organ damage in these conditions are poorly known, however. In particular, there is a paucity of data on the link between chronic inflammation and metabolic disorders. Based on some of our own results and recent developments in our understanding of age-related inflammation as a whole-body response,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 143 publications
0
6
0
Order By: Relevance
“…On the one hand, under aging conditions, changes in tissue structure gradually accumulate towards malignant transformation, leading to increased vascular permeability and extravasation 31 . These changes slow down the transport efficiency of thyroid hormones in the vascular bed and affect their ability to pass through the endothelial barrier 32 . On the other hand, the aging process results in a decrease in the production of thyroid hormones 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, under aging conditions, changes in tissue structure gradually accumulate towards malignant transformation, leading to increased vascular permeability and extravasation 31 . These changes slow down the transport efficiency of thyroid hormones in the vascular bed and affect their ability to pass through the endothelial barrier 32 . On the other hand, the aging process results in a decrease in the production of thyroid hormones 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…According to both our results ( Table 3 , the regression model “C”) and the literature evidence, the frailty status is able to modify correlations between TSH and IL-37. In our recently published review paper, we elaborated the role of TSH—a sign of the activated hypothalamus-pituitary-thyroid (HPT) axis—in conditions associated with inflammation and impaired glucose-related metabolism, such as aging and cardio-metabolic conditions [ 81 ]. In brief, a hypothyroid state in older individuals, indicated by increased TSH, is viewed as the system’s homeostatic reaction which takes place when IL-37, as a major tissue homeostatic mechanism under inflammatory conditions, fails to restore the metabolic costs of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that people with abnormal glucose metabolism have high levels of inflammatory cytokines ( 44 ). The crosstalk between the cytokine IL-37 and thyroid hormones could be the key regulatory mechanism that justifies the glucose metabolic effects ( 45 ). The exact pathophysiological mechanism of glucose metabolism on thyroid hormones resistance needs further research.…”
Section: Discussionmentioning
confidence: 99%